Enhancing the device efficiency by filling the traps in photoanodes - Sudhakar, Vediappan; Krishnamoorthy, Kothandam (Journal of Materials Chemistry C, 2019)
Traps are ubiquitous in semiconductors and act as recombination sites. These recombination sites have a deleterious effect on the device efficiency. Thus, trap filling is used to increase the efficiency of devices. The traps are filled by dopants that either inject or extract electrons to/from the semiconductor. The trap-filled devices exhibit superior performance as compared to their unfilled counterparts. However, to date, this approach has not been explored in dye-sensitized solar cells despite the well-established presence of traps in them. The traps in the TiO2 photoanode are due to the presence of oxygen vacancies. Therefore, herein, we treated the photo anodes with hydrazine and filled the traps that increased all device metrics. Moreover, further sintering of the trap-filled photoanodes in the presence of hydrazine led to the formation of a nitrogen-doped photoanode. The device comprising a nitrogen-doped photoanode exhibited the efficiency increase of 23%. The detailed analysis of the device performance led to the conclusion that trap filling suppressed back electron transfer and increased the photo conversion efficiency.